Sustainable Community Based Tourism Strategy in Meat Tourism Village, Toba Regency, North Sumatra - Pasaribu, Asmara Wildani; Sinulingga, Nora Anisa Br.; Putra, Fajar Ardiansyah (Green Publisher Indonesia, 2025)
This study examines the sustainability of community-based tourism (CBT) in Meat Village, Toba Regency, North Sumatra, with a focus on empowering local communities, especially in decision-making and tourism management. The research aims to assess the current state of CBT in the village and develop strategies to ensure its long-term sustainability. A mixed-method approach, combining quantitative and qualitative techniques, was employed, using questionnaires, in-depth interviews, and Multidimensional Scaling (MDS) for sustainability analysis. The study found that while the community is involved in tourism activities, their participation in decision-making and planning is limited. Key findings include the importance of enhancing women’s empowerment, improving community involvement in decision-making, and strengthening the role of traditional leaders in conflict resolution. The research emphasizes the need for continuous capacity building and decentralization of tourism management to ensure equitable benefits and preserve cultural heritage. The implications of this study suggest that promoting inclusive governance and providing education and training to local communities can improve the sustainability of CBT, leading to more resilient and culturally sensitive tourism development in rural areas like Meat Village.